Addis Ababa’s sefer, iddir, and gebbi: Nuanced reading of complex urban forms - Tola, Anteneh Tesfaye (A+BE | Architecture and the Built Environment, 2023)
Presently, Africa is experiencing rapid urbanization. The history of urbanization indicates that the process transformed the European traditional agrarian ruralbased societies into modern urban-based industries, manufacturing and services. This dissertation problematizes the above two statements—the frequent overemphasis on population growth in connection to rapid urbanization in Africa, the framing of the eminent challenges as solely of economic concerns, and the usual recommendation that the solution is to build and urbanize fast and inexpensively. The second statement exemplifies the most usual tendency of policy makers and governance bodies to pursue European or American references in search of projective logics—remedies against the challenges of ‘rapid urbanization.’ Such casual disregard to the context-specific nature of city making, based on the imprecise premise of rapid urbanization thus seem to keep cities in African countries in a catch-22—a cycle of urbanization processes that threaten the welfare and livelihood of urban dwellers with little to no means. Academic discourse regarding cities in Africa has for long been dominated by development theories that categorize the region in broad strokes as ‘third world,’ ‘developing,’ and recently the ‘global south.’ The contextual variations and rapidly mutating urbanizations of cities in the region are thus overlooked. Various epistemic clusters have caught up with this phenomenon and started calling for new theories, concepts, vocabulary, and analytic tools to be developed. Many scholars hypothesize that transdisciplinary and expansive tactics need to be deployed in order to capture differences and understand nuances that should be integral to the production of knowledge about the ‘other’ territories. Towards this objective, there are ongoing efforts to generate new theories and methodologies across various epistemes such as comparative urbanism, grounded theory, and social anthropology. On the other hand, even though there are longstanding, built-in, cross-disciplinary traditions in their practices, design and architectural research have lagged in this effort. While, for instance, design anthropology and architectural anthropology have been advocated within the field of anthropology as interdisciplinary approaches to complexity, there exists little drive vise versa. Broadly, architectural fieldwork adopts ethnographic techniques such as observation and in-depth interviews and has done so for long; but theories and methodologies that are intent on apprehending the complex and ever-mutating contexts such as cities in Africa are rare. This research is thus motivated by the calls for new concepts and analytic tools for documenting, analysing, and theorizing complex urban territories. With implicit comparative intent, it takes the case of Addis Ababa city and its old and typifying places—sefer, to develop and test a new architectural transdisciplinary research methodology referred, in this dissertation, to as the trinocular. By way of this methodology, it unearths and introduces sefer, iddir, and gebbi of Addis Ababa as not only socio-spatial phenomena but concepts and vocabulary for a located reading of the city itself. These concepts and vocabulary, the current dissertation argues, in both practical and metaphoric sense, should be the starting point of new urban imaginaries for Addis Ababa. Urban planning and housing projections thus, should draw inspiration from these notions and phenomena. The trinocular is a methodology that is grafted from multiple disciplinary traditions and composed of three conceptual viewing lenses or frames of enquiry: cognitive borders—dwellers’ understanding of the limits of their communal environs, social relationships—social networks that are sources of security and social capital for residents, and spatial typologies that embed and characterize these. These lenses are agile and can be dislocated beyond Addis Ababa or the continental region of Africa, especially in research aimed at nuanced reading of urban complexities. In addition to being an architectural methodological advance, the trinocular provides researchers in the field a springboard for more productive collaborative and transdisciplinary engagement and outcomes.